Longitudinal patterns of analgesic and central acting drug use and associated effectiveness in fibromyalgia. (21st November 2012) - Wolfe, F.; Walitt, B.T.; Katz, R.S.; Lee, Y.C.; Michaud, K.D.; Häuser, W.
Abstract: Background: We describe the changing pattern of analgesic and new central acting drug (NCAD) use (pregabalin, duloxetine, milnacipran) in fibromyalgia and measure NCAD effectiveness in clinical practice. Methods: About 3123 US adult patients with fibromyalgia participated in an 11‐year longitudinal study of fibromyalgia outcomes. We assessed severity‐adjusted treatment prevalence and measured the effect of any use of NCAD on pain and fatigue, and functional status using the Health Assessment Questionnaire (HAQ) disability index. Results: In 2010, 46.7% of patients used opioids, including 12.5% who used strong opioids. During the 11 years, severity‐adjusted strong opioid use increased from 6.3% to 11.7% and any opioid use from 40.0% to 46.6%. Nonsteroidal anti‐inflammatory drug (NSAID) use decreased from 74% to 44%. Tricyclic use dropped in half, from 27% to 15%, while NCAD use increased from less than 10% to 39%. The estimated 25th and 50th percentiles for NCAD discontinuation time were 1 and 2.5 years. Overall pain, fatigue and HAQ scores were unchanged over the 11 years. For patients treated with NCAD, pain scores were reduced significantly by 0.17 (0.03, 0.30) units following the start of NCAD, an improvement of 2.8%. Some sensitivity analyses showed improvements of up to 4.3%. There was no significant improvement in fatigue or functional status. Conclusions: There is a changing pattern of drug treatment in fibromyalgia, consisting mostly of decreased NSAID and amitriptyline use and an increase in NCAD. Drug costs are substantially higher because of NCAD use, but we found no evidence of clinical benefit for NCAD compared with prior therapy.